Closing Rice Yield Gaps in Asia 2023
DOI: 10.1007/978-3-031-37947-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Faunal Biodiversity in Rice-Dominated Wetlands—An Essential Component of Sustainable Rice Production

Catherine R. Propper,
Grant Robert Singleton,
Jodi L. Sedlock
et al.

Abstract: Rice agriculture provides wetlands and complex habitats supporting biodiversity. Wetlands associated with rice agriculture since the 1960s have increased by 32% and now form nearly 12% of wetlands globally at a time when vast areas of natural wetlands are being lost. In this chapter, we set our sights beyond Sustainable Development Goal (SDG) 2 that focuses on ending hunger and achieving food security via the promotion of sustainable agriculture. Often, agricultural scientists are so motivated to achieve food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…A recent study has indicated that amphibians are not able to detect and avoid metal or metalloid contamination (particularly arsenic, iron, manganese and nickel) in otherwise suitable habitats [ 44 ], so if pollution does exist, its effect will be made even worse by the fact that so many species are attracted to the area. Indeed, studies on several Asian anuran species have revealed that rice fields attract many frogs, and there was little difference found between fields with no pesticide use and conventional ones (i.e., that use pesticides) [ 45 ]. While species abundance was higher in the “clean” fields, species diversity was higher in the conventional fields, and the authors stipulate that rice agroecosystems play a key role in maintaining amphibian populations, which in turn provide regulatory, provisioning and cultural ecosystem services [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has indicated that amphibians are not able to detect and avoid metal or metalloid contamination (particularly arsenic, iron, manganese and nickel) in otherwise suitable habitats [ 44 ], so if pollution does exist, its effect will be made even worse by the fact that so many species are attracted to the area. Indeed, studies on several Asian anuran species have revealed that rice fields attract many frogs, and there was little difference found between fields with no pesticide use and conventional ones (i.e., that use pesticides) [ 45 ]. While species abundance was higher in the “clean” fields, species diversity was higher in the conventional fields, and the authors stipulate that rice agroecosystems play a key role in maintaining amphibian populations, which in turn provide regulatory, provisioning and cultural ecosystem services [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies on several Asian anuran species have revealed that rice fields attract many frogs, and there was little difference found between fields with no pesticide use and conventional ones (i.e., that use pesticides) [ 45 ]. While species abundance was higher in the “clean” fields, species diversity was higher in the conventional fields, and the authors stipulate that rice agroecosystems play a key role in maintaining amphibian populations, which in turn provide regulatory, provisioning and cultural ecosystem services [ 45 ]. While we did not detect iron in our water samples and the concentrations of arsenic and nickel were well below the recommended thresholds and reported LC50 values, the case of manganese attracts more attention.…”
Section: Discussionmentioning
confidence: 99%